Synthesis, characterisation and electrical properties of pyrochlore materials in Bi₂O₃-CuO-M₂O₅ (M = Ta and Nb) ternary systems - Chon, Mun Ping (2015)
Detailed investigations of phase diagrams and electrical properties of novel pyrochlores in the Bi₂O₃-CuO-M₂O₅ (M = Ta and Nb) ternary systems were presented. The materials were synthesised through solid state reaction. Careful phase identification using X-ray diffraction analysis was performed to confirm the phase purities of the prepared materials and to determine the subsolidus areas in these systems. The Gibbs’ phase rule approach and disappearing phase method were applied for the construction of the phase diagrams. The complete subsolidus ternary phase diagrams of the BCN and BCT systems were determined using various samples which were prepared over a wide range of temperatures, i.e. 700°C-925°C and 700-950°C, respectively. Phase-pure BCN pyrochlores were found to crystallise in cubic symmetry, space group Fd3m, No. 227 with lattice constants in the range of 10.4855 (5) < x < 10.5321 (3). The mechanism of this limited subsolidus series could be represented by a general formula, Bi₃.₀₈₋ₓCu₁.₈₄₊₂ₓ̷₉Nb₃.₀₈₊₇ₓ̷₉O₁₄.₁₆₊₆ₓ̷₉ (0 ≤ x ≤ 0.36). The cubic pyrochlore subsolidus area of BCT system could be described through two compositional variables in an overall general formula of Bi₂.₄₈₊yCu₁.₉₂₋ₓTa₃.₆₊ₓ₋yO₁₄.₆₄₊₃ₓ̷₂-y: 0.00 (1) ≤ x ≤ 0.80 (1) and 0.00 (1) ≤ y ≤ 0.60 (1), respectively. On the other hand, other binary phases of Bi₇Ta₃O₁₈, CuTa₂O₆ were prepared and characterised systematically for their phase formation, structural and electrical performance. Interesting electrical properties were found in BCT cubic pyrochlores for which these materials exhibited semiconducting behaviour with recorded activation energies 0.3-0.4 eV. The dielectric constant, ε’ of BCT material was ~75 with high dielectric losses, in the order of 10ˉ²-10ˉ¹ at room temperature and frequency of 1 MHz. A structurally related monoclinic phase Bi₁.₉₂Cu₀.₀₈(Cu₀.₃Ta₀.₇)₂O₇.₀₆ was discovered and high ε’, ~70 and dielectric loss were also recorded. The ac electrical conductivity of the material corresponded well to power-law frequency dependence with distinctive features of conductivity in different frequency regimes. The cubic phase of BCN materials had a relatively lower activation energy range, 0.2-0.4 eV. Similar electrical behaviour was observed in BCN pyrochlores as to their comparable electrical conductivities to those BCT materials. Meanwhile, the ε’ of BCN materials in the range of 45-70 and high dielectric losses (tan δ) of 0.04-0.12 were found. Scanning electron microscopy was performed in order to study the surface morphologies of the prepared single phase materials. The spherulite shaped grains were randomly distributed with visible pores observed in the materials. Fourier transform infrared spectroscopy (FTIR) was used to qualitatively identify the bond stretching and bending vibration modes of the pyrochlores. Meanwhile, Raman spectroscopy was employed as a complement technique for structural analysis. Thermal analyses showed no phase transition and weight loss in BCT and BCN materials. Good stoichiometry for the prepared compositions was also confirmed using inductively coupled plasma-atomic emission spectroscopy (ICP-AES) by which a close agreement between the experimental and theoretical values were obtained, neither loss of Bi nor Cu was a problem during synthesis. Divalent cations (M), e.g. Zn, Mg, Ni, Ca, Pb and pentavalent cations (N), e.g. Ta and Sb were chemically introduced into selected BCN and BCT materials. A complete substitutional solid solution, Bi₃.₀₈Cu₁.₈₄₋ₓZnₓTa₃.₀₈O₁₄.₁₆ (0.0 ≤ x ≤ 1.84) was obtained; however, only a narrower solid solution limit was found in the BCN system with general formula, Bi₂.₇₂Cu₁.₉₂₋ₓZnₓNb₃.₃₆O₁₄.₄₀ (0.0 ≤ x ≤ 0.4). The recorded activation energies for Zn substituted BCT pyrochlores were in the range of 0.40-1.4 eV. Extensive solid solutions were also found for the Ta replacement by Sb dopant in the BCT system. The resulted activation energies did not change significantly but remained reasonably low, i.e. in the range of 0.30-0.35 eV.